Influence of tool rotational speed on microstructural characteristics and mechanical properties of friction stir processed AA5754 aluminium alloy under overlap configuration - Senthilnathan K; K Thirumavalavan; P Sivaraj (Materials Research Express)
Friction Stir Processing (FSP) is a variant of the Friction Stir Welding (FSW) technique. Recently, FSP has been extensively used to modify the microstructure of many low-temperature alloys and subsequently to enhance the mechanical properties. Dynamic recrystallization caused by the rotating tool is the main reason for modifying (refining) the microstructure in the stir zone. Since this process operates under solid-state conditions, it eliminates many solidification-related problems. In this research work, 6-mm-thick AA5754 aluminium alloy sheets were overlapped to attain a total thickness of 12 mm. A tapered-threaded HSS tool was then used to perform friction stir processing at the center of the overlapped plates using five different rotational speeds. The other parameters were kept constant. This investigation found that a tool’s rotational speed of 700 rpm yielded a defect-free FSP region, likely due to optimum heat generation under this condition. Moreover, the FSP material at 700 rpm exhibited a maximum tensile strength of 245 MPa. This is mainly due to the formation of finer grains and more refined strengthening precipitates in the FSP region. It is concluded that the tool’s rotational speed plays a vital role in heat generation and subsequently influences the microstructure and mechanical properties.